2007
DOI: 10.1115/1.2746920
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow and Wake Transport in a Low-Speed Axial Fan With Inlet Guide Vanes

Abstract: The present study is focused on the analysis of the dynamic and periodic interaction between both fixed and rotating blade rows in a single stage, low-speed axial fan with inlet guide vanes. The main goal is placed on the characterization of the unsteady flow structures involved in an axial flow fan of high reaction degree, relating them to working point variations and axial gap modifications. For that purpose, an experimental open-loop facility has been developed to obtain a physical description of the flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The Reynolds number based on the tip speed and rotor chord length is 1.410 6 , and the tip clearance is 2.3% of the blade height. At nominal conditions, the volumetric flow rate is 16.5 m 3 /s with a total pressure increment of 1150 Pa. More details can be found in [36][37], and the main geometrical parameters are summarized in a table in the figure 2-b. Test sections and data grid on the windows.…”
Section: Low-speed Axial Fanmentioning
confidence: 99%
See 2 more Smart Citations
“…The Reynolds number based on the tip speed and rotor chord length is 1.410 6 , and the tip clearance is 2.3% of the blade height. At nominal conditions, the volumetric flow rate is 16.5 m 3 /s with a total pressure increment of 1150 Pa. More details can be found in [36][37], and the main geometrical parameters are summarized in a table in the figure 2-b. Test sections and data grid on the windows.…”
Section: Low-speed Axial Fanmentioning
confidence: 99%
“…Figure 3 illustrates the degree of convergence achieved with this election. The convergence of the phase-averaged data is presented only for the axial velocity component, which is more restrictive than the tangential one (axial velocity presents higher gradients and fluctuations than the tangential component [36]). The results are presented for two representative points, one placed at midspan and the other in the hub boundary layer (see the dashed lines in the time-averaged contour plot), for both nominal and near stall conditions.…”
Section: Measuring Techniques and Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Mohseni et al [3] presented three different novel IGVs designs for centrifugal compressors and the results showed that the s-cambered profile was preferred for applications with positive prewhirl. Cui [4] and Oro et al [5] focused on the unsteady flow for centrifugal compressors with inlet guide vanes, and analyzed the unsteady flow structures, periodic interaction, and wake transport. Johnston and Fleeter [6] performed experiments on pressure and velocity fields of wake-induced by IGVs for three IGV-rotor axial distances.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies on axial fan-generated flows in the immediate vicinity of the fan have shown that the flow indeed has a non-zero swirl velocity, and that the turbulence is inhomogeneous and anisotropic. 28,29 However, these studies have only focused on the flow field upstream and in close proximity to the fan. To our knowledge, experiments have not been conducted to characterize the turbulent dispersion of passive scalar quantities further downstream from an axial fan.…”
mentioning
confidence: 99%